2019
DOI: 10.1042/bsr20181613
|View full text |Cite
|
Sign up to set email alerts
|

PLCE1 promotes myocardial ischemia–reperfusion injury in H/R H9c2 cells and I/R rats by promoting inflammation

Abstract: Myocardial ischemia–reperfusion (I/R) injury is a major contributor to the morbidity and mortality associated with coronary artery disease. How to ensure the recovery of blood supply to ischemic myocardial tissue while avoiding or reducing I/R injury remains a critical problem in clinical practice. In the present study, we examined the function of phospholipase C ϵ-1 (PLCE1) by an H9c2 H/R (H/R, hypoxia–reoxygenation) model and a rat myocardial I/R injury model. The expression of PLCE1 and its effect on I/R in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 32 publications
(30 reference statements)
0
25
0
1
Order By: Relevance
“…Cell culture. H9C2 cells were cultured in a hypoxic culture chamber (37˚C, 2.5% O 2 , 5% co 2 , 92.5% N 2 ) to establish a cellular model of MI (35). Cells in the control group were cultured in a normal culture chamber (37˚C, 5% CO 2 ).…”
Section: Reverse Transcription-quantitative (Rt-q) Pcrmentioning
confidence: 99%
“…Cell culture. H9C2 cells were cultured in a hypoxic culture chamber (37˚C, 2.5% O 2 , 5% co 2 , 92.5% N 2 ) to establish a cellular model of MI (35). Cells in the control group were cultured in a normal culture chamber (37˚C, 5% CO 2 ).…”
Section: Reverse Transcription-quantitative (Rt-q) Pcrmentioning
confidence: 99%
“…Human ADSC-CM has a therapeutic effect on mouse ischemic stroke models mainly by reducing nerve cell apoptosis and increasing endothelial cell proliferation 24 . Bone marrow mesenchymal stem cell conditioned medium (BMSC-CM) reduced hypoxia-induced cardiomyocyte apoptosis 28 . Our previous study showed that ADSC-CM protected against I/R-induced injury in skin flaps 29 .…”
Section: Discussionmentioning
confidence: 99%
“…For the transfection, the recombinant plasmid pBLG-TAP-EGFP-N1 was transiently transfected into mice using in Entranster- in vivo transfection reagent (Engreen Biosystem, Beijing, China) according to the manufacturer's instructions. Numerous studies have shown that the transfection agent causes limited inflammation in mice and rats ( 20 , 21 ). In brief, the mice in the prevention and treatment groups were injected with 150 μl of transfection master mix containing 18.75 μg of DNA, 37.5 μl of transfection reagent, 75 μl of 10% glucose solution, and 37.5 μl of double-distilled water, via caudal vein.…”
Section: Methodsmentioning
confidence: 99%